The impact of moisture on thermal conductivity of fabrics - Slavinec, Mitja; Repnik, Robert; Klemenčič, Eva (Anali PAZU, 2022)
The article presents the experimental results of the thermal conductivity of absorbent fabrics for increasing relative amount of water in the fabric. Measurements confirm that the effective thermal conductivity of fabrics at low moisture level is proportional to the relative amount of water absorbed in fabrics. With increasing relative amount of water in the fabric, effective thermal conductivity stabilizes around the value comparable with the thermal conductivity of water. The experimental results are compared with the theoretical linear model.
Keywords: heat; heat conduction; thermal conductivity; absorbent fabrics